2022
DOI: 10.3390/ph16010039
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Neuroprotective Mechanism of Curcumin Inhibition of Intestinal Inflammation against Parkinson’s Disease Based on the Gut-Brain Axis

Abstract: Parkinson’s disease (PD) is a chronic progressive neurodegenerative disease commonly seen in aged people, in which gastrointestinal dysfunction is the most common nonmotor symptom and the activation of the gut–brain axis by intestinal inflammation may contribute to the pathogenesis of PD. In a previous study, curcumin was considered neuroprotective in PD, and this neuroprotective mechanism may act by inhibiting intestinal inflammation. Therefore, the aim of this study was to evaluate the effect of curcumin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 103 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…The concentrations of SCFAs were significantly lower in samples of patients with PD ( Jiang et al, 2023 ). The pro-inflammatory state in the colon of patients with PD persists due to decreased abundance of SCFA-producing colonic bacteria in colon tissues of subjects with PD, which was an important and early pathogenesis of Parkinson’s disease ( Agirman et al, 2021 ; Zhou et al, 2021 ; Zhong et al, 2022 ; Jiang et al, 2023 ). The function of SCFA in Parkinson’s disease may be related to CD3 + T cells, TLR4 + cells, and depend on the gut-brain axis ( Perez-Pardo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentrations of SCFAs were significantly lower in samples of patients with PD ( Jiang et al, 2023 ). The pro-inflammatory state in the colon of patients with PD persists due to decreased abundance of SCFA-producing colonic bacteria in colon tissues of subjects with PD, which was an important and early pathogenesis of Parkinson’s disease ( Agirman et al, 2021 ; Zhou et al, 2021 ; Zhong et al, 2022 ; Jiang et al, 2023 ). The function of SCFA in Parkinson’s disease may be related to CD3 + T cells, TLR4 + cells, and depend on the gut-brain axis ( Perez-Pardo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results, including the trajectory, total distance, and average speed of the mice, were recorded and analyzed using the SMART 3.0 system. The field was cleaned using 70% alcohol before each use ( Zhong et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin (1,7‐bis(4‐hydroxy‐3methoxyphenyl)‐1,6‐heptadiene‐3,5‐dione, CUR), a natural polyphenol isolated from turmeric, has been found to possess important pharmacological properties and low toxicity which makes it promising to use in the complex therapy of various pathologies (Sohn et al, 2021; Urošević et al, 2022). Clinical trials have already shown some positive results when using curcumin in the treatment of Alzheimer's (Teter et al, 2019), Parkinson's (Zhong et al, 2022), HIV (Butnariu et al, 2022), coronavirus COVID‐19 (Ahmadi et al, 2021; Vahedian‐Azimi et al, 2022), cancer (Arslan et al, 2022; Mortezaee et al, 2019) and cardiovascular (Cox et al, 2022; Li et al, 2020) diseases.…”
Section: Introductionmentioning
confidence: 99%